1988
DOI: 10.1002/hep.1840080233
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of the guanase screening test in donor blood for prevention of posttransfusional non-A, non-B hepatitis

Abstract: We adopted an automated method for measuring guanase in donor blood and examined the incidence of posttransfusional non-A, non-B hepatitis when donor blood with high guanase activities was excluded. Sixty-seven (2.4%) of 2,826 units were excluded from use in transfusion because they had guanase activities above 1.71 units per liter. Of 112 recipients, 8 (7%) developed posttransfusional non-A, non-B hepatitis. The incidence of posttransfusional non-A, non-B hepatitis was 17% before adoption of the guanase scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Thus a high serum guanase level is considered to be a specific indicator of hepatocellular damage (4,6,16,18). Moreover, Yamasaki et al (20), Mihara et al (17) and Ito et al (11) reported that the incidence of posttransfusional non-A, non-B hepatitis (PTH) was significantly higher in recipients of blood with high guanase activity, and that PTH could be prevented by avoiding use of donor bloods with high guanase activities (12).…”
Section: Humanmentioning
confidence: 99%
“…Thus a high serum guanase level is considered to be a specific indicator of hepatocellular damage (4,6,16,18). Moreover, Yamasaki et al (20), Mihara et al (17) and Ito et al (11) reported that the incidence of posttransfusional non-A, non-B hepatitis (PTH) was significantly higher in recipients of blood with high guanase activity, and that PTH could be prevented by avoiding use of donor bloods with high guanase activities (12).…”
Section: Humanmentioning
confidence: 99%
“…4 A variety of pathogens are dependent upon the host’s purine salvage pathway for the nucleotides necessary for their survival, as they do not possess a de novo purine biosynthesis mechanism. 58 It was demonstrated that inhibition of GDA could be caused selectively in pathogens without affecting the mammalian biosynthesis of nucleic acids. 9 Therefore, a new chemotherapeutic strategy lies in the search for drugs that selectively block the parasite from the pathway that is required for its survival.…”
mentioning
confidence: 99%
“…Reaction of 5 with acetic anhydride afforded the N 5 -acetyl derivative 6 in 81% yield. Compound 6 was alkylated at N 5 position with 1,1-diethoxy-2-iodoethane 31 employing potassium carbonate in DMF and 18- crown-6 to provide 7 in 66% yield. 29 The N 5 -acetyl group was then removed by treatment with sodium ethoxide in ethanol to obtain 8 in 84% yield.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of posttransfusion hepatitis are now consid ered to be of the non-A, non-B variety [1,4,5], This form is thought to progress to a chronic condition [6][7][8][9], and the possibly gives rise to hepatocellular carcinoma [10,11], The risk factors of posttransfusion hepatitis have been investigated in regard to age and sex of recipients [6.12], serum alanine aminotransferase (ALT) [13], anti-HBc [14], anti-HBs [15] and guanase activity [16] of donated blood, and the volume of transfusion. To assess the risk of development of this disease.…”
Section: Introductionmentioning
confidence: 99%